2016
DOI: 10.4236/am.2016.718185
|View full text |Cite
|
Sign up to set email alerts
|

Combined Effects of Thermal Diffusion and Diffusion-Thermo Effects on Transient MHD Natural Convection and Mass Transfer Flow in a Vertical Channel with Thermal Radiation

Abstract: We study the nonlinear coupled evolution equations which model the transient MHD natural convection and mass transfer flow of viscous, incompressible and electrically conducting fluid between two infinite vertical plates in the presence of the transversal magnetic field, thermal radiation, thermal diffusion and diffusion-thermo effects. Both analytical and numerical methods are used for this study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…In some of the above mentioned studies, the authors discussed the effect of thermal radiation using linearized Rosseland heat diffusion and this was later faulted by Magyari and Pantokratoras [28] on the basis that it does not reflects the real mechanism in heat transfer characteristics in most boundary layer flows with thermal radiation and they therefore gave alternative approach using non-linear Rossland heat diffusion. In apprehension of this achievement, correlated studies can be observed in Yabo et al [29], Jha et al [30] and Ajibade and Bichi [31]. This paper investigates variable fluid properties on steady natural convection Couette flow through a vertical porous channel.…”
Section: Introductionmentioning
confidence: 89%
“…In some of the above mentioned studies, the authors discussed the effect of thermal radiation using linearized Rosseland heat diffusion and this was later faulted by Magyari and Pantokratoras [28] on the basis that it does not reflects the real mechanism in heat transfer characteristics in most boundary layer flows with thermal radiation and they therefore gave alternative approach using non-linear Rossland heat diffusion. In apprehension of this achievement, correlated studies can be observed in Yabo et al [29], Jha et al [30] and Ajibade and Bichi [31]. This paper investigates variable fluid properties on steady natural convection Couette flow through a vertical porous channel.…”
Section: Introductionmentioning
confidence: 89%
“…In order to decouple the system of Equations ( 6)-( 8), a small non-zero parameter e is used such that the Soret and Dufour parameters are of order OðeÞ (Ahmad et al, 2016). Perturbation method has been used to write the analytical solution of the problem utilizing the fact that Soret and Dufour parameters are small (Isah et al, 2016;Lagra et al, 2018;Makinde, 2011;Reddy, 2016; Uwanta & Usman, 2014).…”
Section: Analytical Solutionsmentioning
confidence: 99%
“…Although the magnitudes of the two effects are small, however, they have been seen to have direct relevance in systems where density differences in the flow region exist such as in petrology, isotopes separation, hydrology, chemical processing, geoscience among others (Ashyralyev & Gambo, 2016;Isah, Jha, & Jeng-Eng, 2016;Jha & Gambo, 2019;Omowaye, Fagbade, & Ajayi, 2015;Tippa, Narahari, & Rajashekhar, 2014;Uwanta & Usman, 2014). Several studies reveal that free convection heat and mass transfer flow can be affected by Soret effect, Dufour effect or the combination of the two (Bourich, Hasnaoui, Mamou, & Amahmid, 2004;Isah et al, 2016;Jha & Gambo, 2019;Kafoussias & Williams, 1995;Lagra, Bourich, Hasnaoui, Amahmid, & Er-Raki, 2018;Mortimer & Eyring, 1980;Omowaye et al, 2015;Raju, Narahari, & Rajashekhar, 2014;Reddy, 2016;Soret, 1979;Tippa et al, 2014;Uwanta & Usman, 2014). However, when the two effects are combined, the resulting system of governing equations becomes highly complicated and its analytical solution has been an outstanding challenge in heat and mass transfer process.…”
Section: Introductionmentioning
confidence: 99%
“…They therefore proposed alternative method which adopted the use of nonlinear temperature in the expression for thermal radiation. In recognition to this, connected studies can be witnessed in Ajibade (2018a, 2020), Ajibade and Yusuf (2019), Yabo et al (2016) and Jha et al (2017).…”
Section: Introductionmentioning
confidence: 96%